Comparison of Clusterization of Higher Education Institutions in Regions XII Maluku and North Maluku based on the Science and Technology Index (Sinta) - Kolengsusu, Haris; Henaulu, Agung K; Mony, Farida (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research aims to analyze the comparison of clustering results of universities based on data sourced from the Science and Technology Index (Sinta). The analysis results will serve as a guide for all higher education institutions in the XII Maluku and North Maluku regions to improve their performance in the three pillars of higher education to achieve better clustering. This study was conducted by extracting Sinta data from the years 2019 to 2021. The research results show that based on the Total All Score, the universities in Maluku are ranked in descending order from the highest to the lowest score. The main cluster is occupied by Pattimura University with a total score of 16.04, followed by State Polytechnic of Ambon with a total score of 13.45. In the middle cluster, we have Indonesian Christian University of Maluku with a total score of 9.19, and in the basic cluster, we have Darussalam Ambon University with a total score of 6.62, Maluku Husada Health Sciences Institute with a total score of 4.79, Doktor Husni Ingratubun Tual University with a total score of 2.5, and Institute of Technology and Business, Ambon School of Computer Science with a total score of 2.37. As for North Maluku, the universities are ranked in descending order from the highest to the lowest score. The main cluster is led by Universitas Kharun with a total score of 14.01. In the middle cluster, we have Muhammadiyah University of North Maluku with a total score of 11.62, and Halmahera University with a total score of 9.45. In the basic cluster, we have Nuku University with a total score of 5.45, Pasifik Morotai University with a total score of 5.3, Hein Namotemo University with a total score of 4.63, and Bumi Hijrah University Tidore with a total score of 3.31